Financing the healthcare system in Ukraine under modern challenges: models, sources and problems - Чеберяко, Оксана Вікторівна; Колесник, Віктор Федорович (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . Studying the financing of the health care system in the context of modern challenges and comparing models will help identify the key problems inherent in the system and identify ways to overcome them, in particular, regarding the availability of quality medical care for all segments of the population at the expense of various sources of funding. Russia's large-scale war against Ukraine has disrupted access to health care through infrastructure damage, loss of personnel, security issues, mass displacement of the population, and increased costs of medical resources, combined with a decrease in the population's ability to pay for medical services. Even before the war, the healthcare system needed significant reforms and transformation of its financing model. In view of the above-mentioned problems, it is advisable to study the foreign experience of health care financing models and implement the best practices in Ukraine in the post-war period. M e t h o d s . The materials of the research are regulatory and legal support for the financing of the health care system in Ukraine and the work of domestic and foreign scientists who carry out their scientific and practical research in the field of models, sources and problems of financing the health care system in the conditions of new challenges. In the process of carrying out the research, the following scientific methods were used: theoretical generalization and grouping (to characterize the main economic models of health care financing, sources of financing, delineation of health care expenditures between budgets, as well as determination of health care expenditures by software feature); formalization, analysis and synthesis (for the analysis of total health care costs in % of GDP in OECD countries); logical generalization of results (formulation of conclusions). R e s u l t s . Different models of health care systems exist in the world, and theoretical and practical aspects of financing the health care system in Ukraine in the conditions of new challenges are highlighted. The dynamics of budgetary financing of the health care system, the structure and composition of expenditures of the State and local budgets for health care are analyzed. The peculiarities of health care expenditures in the conditions of the Covid-19 pandemic and large-scale war are highlighted. The peculiarities of health care expenditures in the conditions of the Covid-19 pandemic and large-scale war are highlighted. The main problems were revealed and the ways of improving the health care financing system in the post-war period were formed. C o n c l u s i o n s . The global Covid-19 pandemic and the large-scale war on the territory of Ukraine significantly affected the financing of the health care system. The hostilities caused an increase in the costs of financing the health care system, and only an increase in this group of costs is predicted in the future. Healthcare financing in Ukraine in the post-war period plays a key role not only in the restoration of the medical infrastructure, but also in the general system of providing medical services. The post-war reconstruction of health care requires significant investments, the involvement of international aid, public-private partnerships and effective management of internal resources to restore and modernize the infrastructure, the introduction of modern medical technologies and digital solutions to improve the efficiency of the provision of medical services.

В с т у п . Дослідження питання фінансування системи охорони здоров'я та порівняння моделей допоможе виокре мити основні проблеми, виокремити шляхи їх подолання, зокрема щодо доступності якісної медичної допомоги для всіх верств населення за рахунок різних джерел фінансування. Війна росії проти України порушила доступ до медичних послуг через пошкодження інфраструктури, втрату персоналу, проблеми з безпекою, масове переміщення населення, збільшення витрат на медичні ресурси в поєднанні зі зниженням платоспроможності населення за медичні послуги. М е т о д и . Матеріалами дослідження є нормативно-правове забезпечення щодо фінансування системи охорони здоров'я в Україні, праці вітчизняних і зарубіжних вчених у сфері моделей, джерел та проблем фінансування системи охорони здоров'я в умовах нових викликів. У процесі здійснення дослідження було використано такі наукові методи: теоретичного узагальнення та групування (для характеристики основних економічних моделей, джерел фінансування охорони здоров'я, розмежування видатків у цій сфері між бюджетами, визначення видатків на охорону здоров'я за програмною ознакою); формалізації, аналізу та синтезу (для аналізу загальних витрат на охорону здоров'я у % від ВВП в країнах ОЕСР); логічного узагальнення результатів (формулювання висновків). Р е з у л ь т а т и . Висвітлено різні моделі систем охорони здоров'я, які існують у світі, теоретичні та практичні аспекти фінансування цієї системи в Україні, проаналізовано динаміку бюджетного фінансування, структуру і склад видатків Державного та місцевих бюджетів на охорону здоров'я. Виокремлено особливості цих видатків в умовах пандемії Covid-19 та війни. Розкрито основні проблеми та сформовано шляхи вдосконалення системи фінансування охорони здоров'я в повоєнний період. В и с н о в к и . Світова пандемія Covid-19 і війна на території України суттєво вплинули на фінансування системи охорони здоров'я. Бойові дії спричинили збільшення витрат на фінансування й надалі прогнозується лише збільшення цієї групи видатків. Фінансування охорони здоров'я у повоєнний період відіграє ключову роль не лише у відновленні медичної інфраструктури, а й загальної системи надання медичних послуг. Повоєнна реконструкція охорони здоров'я потребує значних інвестицій, залучення міжнародної допомоги, державно-приватного партнерства й ефективного управління внутрішніми ресурсами для відновлення та модернізації інфраструктури, впровадження сучасних медичних технологій та цифрових рішень для підвищення ефективності надання медичних послуг.
Фінансування системи охорони здоров'я в Україні в умовах сучасних викликів: моделі, джерела та проблеми
Keywords: health care system; forms of financing; market model; public-private model; state budget; local budgets; social model; система охорони здоров'я; форми фінансування; ринкова модель; соціальна модель; суспільно-приватна модель; державний бюджет; місцеві бюджети; система охорони здоров'я; форми фінансування